Recent advances and opportunities in planning green petroleum supply chains: a model-oriented review. Issue 6 (18th August 2021) - Abdussalam, Otman; Trochu, Julien; Fello, Nuri; Chaabane, Amin
ABSTRACT: Today, petroleum companies cannot be competitive and efficient without considering potential solutions provided by sustainable supply chain management (SSCM) optimization models. SSCM can solve different challenges faced by this sector. Academics and practitioners consider the opportunities offered by decision-making tools for planning sustainable petroleum supply chains. Moreover, the ever-increasing number of publications applying decision-making models to the petroleum industry also attests to this fact. Therefore, the primary objective of this study is to understand the evolution of sustainable supply chain planning in the petroleum industry and highlight the specificities of the body of knowledge in this area. A comprehensive analysis is performed using 23 papers published from 2010 to 2019. This paper proposes a classification framework to analyze different factors in developing mathematical models, including the triple bottom line pillars of sustainability (economic, environmental, and social). The main observation is that planning models that focus on all three sustainability dimensions in the petroleum sector are scarce. Regarding the environmental dimension, the analysis demonstrates that consideration of greenhouse gas emissions, especially CO2 impacts, is dominating planning models. Furthermore, there is an absence of quantitative models that include social dimensions, and this gap must be addressed in the future. Finally, we propose future extensions to develop research in SSCM in the petroleum sector, keeping in mind recent developments from both technological and economic drivers in this specific sector.